Perancangan User Experience Aplikasi Forum Dan Jual Beli Bibit Tanaman Dengan Menggunakan Human-Centered Design - Galistyawan Caesanova; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The COVID-19 pandemic has given birth to the trend of caring for plants. The demand for plant seeds for plant sellers increased. However, several obstacles arise such as low ability to bargain for products, lack of available market information, and lack of clarity on the product marketing network. This happens because of the limited reach of marketing and no place to wider their market. The design of the application user experience on the android system can be an answer to this problems by creating forum for product marketing from seed traders to buyers and by a forum for mutual questions and answer discussion. This research using the Human-Centered Design (HCD) approach. The results of usability testing evaluations by traders get 100% effectiveness, time base efficiency 0.10054 goals/sec, with the predicate SUS excellent and for attractiveness aspects 2.23, praise 2.15, efficiency 2.10, accuracy 2.10 , stimulation 2.20, novelty 1.90. testing on buyers, 100% effectiveness, 0.201 efficiency, system usability scale 8.3 with very good category, and user experience questionnaire on aspects of attractiveness 2.23, game 2.75, efficiency 2.20, accuracy 2.25, stimulation 2.30, and novelty 0.90. The Buyer User Experience Questionnaire was in the very good category except for novelty getting above average.